Biogas production from ensiled maize with and without hydrothermal pretreatment - Koponen, Hanna (2010)
Energy crops are suitable substrates for anaerobic digestion. In the future their use will probably increase, and among other things optimum storage and pretreatment technologies should be developed. In this study eight maize silage varieties grown in Piikkiö, Southern Finland were used as substrates in anaerobic digestion. Also hydrothermal pretreatment was used to improve the biogas yield. Composition of the maize silage and the pretreated maize silage were analyzed and inhibitors were analyzed from the pretreated maize silage. The maize silages produce methane as much as fresh maizes in previous studies, when losses during the ensiling are taking into account and even 25-50 % more when losses were ignored. KXA7251 produced most methane per volatile solids analyzed before ensiling (VSoriginal) (408±7 l CH4/kgVS) and per cultivation area, whereas Amara produced most methane per volatile solids analyzed after ensiling (VSadded) (470±4 l CH4/kgVS). Howev-er, no variety jumps out when comparing the results of this study and the results of pre-vious studies for fresh maizes. The pretreated silages produce less methane than the un-treated silages, probably because of inhibition. Probable reasons for the inhibition were furans and carboxylic acids. More cellulose, insoluble lignin and ash were analyzed from the solid fraction of the pretreated silage than from the untreated silage, probably caused by hemicellulose degradation during the pretreatment.